2009
DOI: 10.1080/10400430902945678
|View full text |Cite
|
Sign up to set email alerts
|

Use of MMG Signals for the Control of Powered Orthotic Devices: Development of a Rectus Femoris Measurement Protocol

Abstract: A test protocol is defined for the purpose of measuring rectus femoris mechanomyographic (MMG) signals. The protocol is specified in terms of the following: measurement equipment, signal processing requirements, human postural requirements, test rig, sensor placement, sensor dermal fixation, and test procedure. Preliminary tests of the statistical nature of rectus femoris MMG signals were performed, and Gaussianity was evaluated by means of a two-sided Kolmogorov-Smirnov test. For all 100 MMG data sets obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Five studies [28], [43], [102]- [104] were found related to MMG-based switch control or externally powered prosthesis control (Table XVI). Antonelli et al [102] set a protocol for MMG signal recorded by an accelerometer on the RF muscle in order to control orthotic devices.…”
Section: ) Mmg Assisted Externally Powered Prosthesis And/or Switch mentioning
confidence: 96%
See 1 more Smart Citation
“…Five studies [28], [43], [102]- [104] were found related to MMG-based switch control or externally powered prosthesis control (Table XVI). Antonelli et al [102] set a protocol for MMG signal recorded by an accelerometer on the RF muscle in order to control orthotic devices.…”
Section: ) Mmg Assisted Externally Powered Prosthesis And/or Switch mentioning
confidence: 96%
“…Antonelli et al [102] set a protocol for MMG signal recorded by an accelerometer on the RF muscle in order to control orthotic devices. They investigated mean RMS value, skewness, kurtosis, and power spectral density (PSD) of the MMG signal.…”
Section: ) Mmg Assisted Externally Powered Prosthesis And/or Switch mentioning
confidence: 99%
“…MMG has been applied in the study of contractile properties of muscle McAndrew et al, 2006;Cramer et al, 2004;Madeleine et al, 2007), myopathies (Barry et al, 1990;Rhatigan et al, 2007;Orizio et al, 1997), fatigue (Shinohara and Sogaard, 2006;Madeleine et al, 2002;Kimura et al, 2008;Itoh et al, 2004), and as a control input to upper extremity prostheses and switches (Silva et al, 2005;Barry et al, 1986;Antonelli et al, 2009;Alves and Chau, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…In this setting, simple MMG triggered prosthetics have been developed [18][19][20] and work has been done in classifying the MMG signal into grasping-motion classes [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%